Aluminum-Doped SnO2 Hollow Microspheres as Photoanode Materials for Dye-Sensitized Solar Cells. (9th June 2016) - Xu, Binghua; Chen, Zeng; Li, Shengjun
Abstract : Al doped SnO2 microspheres were prepared through hydrothermal method. As-prepared SnO2 microspheres were applied as photoanode materials in dye-sensitized solar cells (DSCs). The properties of the assembled DSCs were significantly improved, especially the open-circuit voltage. The reason for the enhancement was explored through the investigation of dark current curves and electrochemistry impedance spectra. These results showed that the Al doping significantly increased the reaction resistance of recombination reactions and restrained the dark current. The efficient lifetime of photoexcited electrons was also obviously lengthened.